Evolution of Fascial Closure Optimization in Damage Control Laparotomy. Issue 12 (December 2016) - Lauerman, Margaret H.; Dubose, Joseph J.; Stein, Deborah M.; Galvagno, Samuel M.; Bradley, Matthew J.; Diaz, Jose; Scalea, Thomas M.
Management of patients undergoing damage control laparotomy (DCL) involves many surgical, medical, and logistical factors. Ideal patient management optimizing fascial closure with regard to timing and closure techniques remains unclear. A retrospective review of patients undergoing DCL from 2000 to 2012 at an urban Level I trauma center was undertaken. Mortality of DCL decreased over the study period from 62.5 to 34.6 per cent, whereas enterocutaneous fistula rate decreased from 12.5 to 3.8 per cent. Delayed primary fascial closure rate improved from 22.2 to 88.2 per cent. Time to closure ( P < 0.001), time to first attempted closure ( P < 0.001), and number of explorations ( P < 0.001) were associated with ability to achieve delayed primary fascial closure. In subgroup analysis, achievement of delayed primary fascial closure was decreased with time to closure after one week (91.7% vs 52.0%, P = 0.002) and time to first attempted closure after two days (86.5% vs 70.0%, P = 0.042). In multivariate analysis, time to closure (odds ratio: 0.13, 95% confidence interval: 0.04–0.39; P < 0.001) and time to first attempted closure (odds ratio: 0.61, 95% confidence interval: 0.37–0.99; P = 0.046) were the only factors associated with achieving delayed primary fascial closure. Timing of attempted closure plays a significant role in attaining delayed primary fascial closure, highlighting the importance of early re-exploration.